Socialization of Elementary School PJOK Teachers in the Southern City of Cimahi through Pickleball Sports - Yudi Hidayat; Sumbara Hambali; Gugun Gunawan; Ricky Ferrari Valentino; M Saleh Paembonan; Dindin Bernhardin; M Syahnal Rambe (CV Media Inti Teknologi, 2024)
The aim of carrying out this community service activity is to provide knowledge and information about new types of sports that are currently popular with many people in all circles, and one of them is introducing the sport of Pickleball. Some of the implementation methods for this activity are delivery using lecture, discussion and question and answer methods, as well as direct demonstrations or practice. This research was carried out at Melong Mandiri 3 Elementary School, Cimahi City, involving one regional branch of South Cimahi City with a total of 7 schools involved. The results of this research show that what is proposed in this community service activity plan can be implemented well and fulfilled. From the results of the implementation of this activity, it was found that the majority of PJOK teachers in the South Cimahi area were still unfamiliar with the sport of pickleball because, from the test results using questions, an average of 85.7% of the 15 people present were not familiar with the sport of pickleball. Therefore, after being given this socialization material, the participants had quite a high enthusiasm for learning about the sport of pickleball.